G147 Experiences and perspectives of adolescents presenting to sexual assault referral centres. (27th April 2015) - Clarke, V; Armitage, AJ; Kramer, T; Wellings, K; Goddard, A; Welch, JM; Viner, RM; Khadr, SN
Abstract : Background: Adolescent sexual assault victims are a vulnerable group with a high baseline prevalence of mental health problems and low follow-up rates. Little is known about their experience of services following sexual assault. Aims: To evaluate experiences of care among adolescents accessing co-ordinated specialist sexual assault services serving a large UK city. Methods: Design : Prospective longitudinal cohort study. Study population : Adolescents aged 13–17 years presenting to a sexual assault referral centre (SARC) within six weeks of assault. Participants evaluated care received from different professionals using a questionnaire adapted from the Commission for Health Improvement Experience of Service Questionnaire (CHI-ESQ). Results: 30% consented to take part. Data were analysed for the first 64 study participants, evaluating care received from uniformed police (n = 51), specialist sexual offences investigative techniques (SOIT) officers (n = 58) and clinical staff at the SARCs (doctors and crisis workers, n = 64). 97% were police referrals and 3%, self-referrals. 67% had experienced vaginal rape, 32%, oral rape and 12%, anal rape. 90% underwent a forensic medical examination. Commonly held fears before accessing care were that they would be judged, disbelieved, 'blamed' or 'called a liar'. Many participants were apprehensive that the forensic examination would be painful, embarrassing or reveal health problems such as infections. As shown in Figure 1, care given by clinical staff at SARCs was consistently rated higher than police care. Only 49% found uniformed police easy to talk to and only 64% felt safe in their care. Only 63% felt believed by their SOIT officer and only 59% felt they had been given enough information (Figure 1 ). Conclusions: Many participants described positive experiences of systems of care for victims of sexual assault. However, variable experiences of care between services highlight the need for improvement in specific areas. Anxieties about being blamed or judged may prevent adolescents accessing services following sexual assault.